VALUE CHAIN DEVELOPMENT AS ALTERNATIVE METHOD FOR MAPPING WASTE MANAGEMENT - Muhammad Saiful Hakim; Imam Baihaqi; Aang Kunaifi (Journal of Innovation in Business and Economics, 2017)
Solid Waste management begin at the household as waste of consumption and ended as a new form of waste product or recycling. Based on its value chain the subsequent process will have distict differences with manufacturing product. Value chain of manufacturing product will characterize as value added chain along the chain, where every side of the chain will generate positive chain. In the other hand, some parties of waste management value chain will negative value existed. Some parties in this chain will generate negative value solely because they must establish some cost for wipe the waste. Dissimilarities between value chain on product and waste will contribute to discrepancy between parties. Main purpose of this research is to identify value chain from solid waste management using value chain development. Another purpose to accomplished is to resolve discrepancy in value chain.  Research results shown that household is the parties that experiences negative value. To minimize the discrepancies there should be an action towards household